Geologi dan Karakteristik Laterit Nikel Berdasarkan Mineralogi Batuan Dasar dan Geokimia Daerah Routa dan Sekitarnya, Kecamatan Routa, Kabupaten Konawe, Provinsi Sulawesi Tenggara - Handika, Erdin Tri; Sutarto, Sutarto; Soesilo, Joko (Jurnal Ilmiah Geologi PANGEA, 2024)
The main nickel production in Indonesia mostly comes from laterite deposits that are widely found in eastern Indonesia. The research was conducted in the Konawe area, Southeast Sulawesi which is geologically composed of ultramafic rocks in the form of peridotite (harzburgite, lherzolite, wehrlite), dunite, websterite, and others. These ultramafic rocks are bedrock that has the potential to form nickel laterite deposits. To find out the characteristics of nickel laterite deposits, surface mapping, subsurface mapping or sub-surface mapping were carried out by drilling to determine the subsurface conditions, and statistical data processing in the form of geochemical data of the elements MgO, SiO2, Al2O3, Fe, Ni, MnO, Co, and Cr2O3. From the data, it is known that the research area is dominated by the Routa Peridotite Unit which has olivine and ortho-pyroxene mineral content based on petrographic analysis so that the enrichment of Ni content produced in the laterite zone is high. The research area has a thick and complete laterite zone where there is a cover soil zone consisting of Top Soil (SO), and Ferricrete (FE), a limonite zone consisting of Ferrigenous Zone (FZ), Transported limonite (TL), Limonite (LM), a saprolite zone consisting of Ferrigenous Saprlote (FS), Saprolite (SP), Rocky Saprolite (RS), Saprolite Rock (SR), bedrock zone. Based on drilling data, there is a thick limonite zone with mineral content in the form of hematite, goethite, manganese, maghemite, and several silica veins or silica boxwork are found which are characteristics of nickel oxide or oxide deposits and in the saprolite zone, garnierite minerals and serpentine minerals are found which are characteristics of hydrous Mg-Silicate nickel laterite deposits. Based on the correlation of drilling data, there is a thick laterite zone formed in flat to sloping morphology, while a thin laterite zone is formed in sloping to steep areas.